Influences of pulse shaping, diversity techniques and channel coding on the performance of DS-CDMA systems - Kok, Boon Kiong. (2008)
The thesis details three areas of study in the DS-CDMA technology. The effect of chip waveforms on the bit error probability performance of a wireless DS-CDMA system is examined. The throughput of a system employing different chip waveforms is further investigated to obtain the system performance under different offered traffic conditions. The final topic discusses the introduction of channel coding to selection diversity and maximum ratio combining of spread-spectrum diversity and antenna diversity. The complexity-performance tradeoff of these combining techniques and the performance gain derived from the incorporation of forward error correction coding are highlighted.